Different patterns of short-term memory deficit in Alzheimer's disease, Parkinson's disease and subjective cognitive impairment. (November 2020) - Zokaei, Nahid; Sillence, Annie; Kienast, Annika; Drew, Daniel; Plant, Olivia; Slavkova, Ellie; Manohar, Sanjay G.; Husain, Masud
Abstract: It has recently been proposed that short-term memory (STM) binding deficits might be an important feature of Alzheimer's disease (AD), providing a potential avenue for earlier detection of this disorder. By contrast, work in Parkinson's disease (PD), using different tasks, has suggested that the STM impairment in this condition is characterised by increased random guessing, possibly due to fluctuating attention. In the present study, to establish whether a misbinding impairment is present in sporadic late-onset AD (LOAD) and increased guessing is a feature of PD, we compared the performance of these patient groups to two control populations: healthy age-matched controls and individuals with subjective cognitive impairment (SCI) with comparable recruitment history as patients. All participants performed a sensitive task of STM that required high resolution retention of object-location bindings. This paradigm also enabled us to explore the underlying sources of error contributing to impaired STM in patients with LOAD and PD using computational modelling of response error. Patients with LOAD performed significantly worse than other groups on this task. Importantly their impaired memory was associated with increased misbinding errors. This was in contrast to patients with PD who made significantly more guessing responses. These findings therefore provide additional support for the presence of two doubly dissociable signatures of STM deficit in AD and PD, with binding impairment in AD and increased random guessing characterising the STM deficit in PD. The task used to measure memory precision here provides an easy-to-administer assessment of STM that is sensitive to the different types of deficit in AD and PD and hence has the potential to inform clinical practice.